ANALISIS DAYA SAING PRODUK ANYAMAN INDONESIA DAN CINA DI PASAR AMERIKA SERIKAT - Ni Ketut Budiningsih; I Gede Putu Hendra Wijaya Kusuma (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to analyze the competitiveness of Indonesian and Cina woven products in the United States market. Competitiveness is analyzed using Revealed Competitive Advantage (RCA). The results of the calculation of Indonesia's RCA show that Indonesia's RCA index for woven products is 3.136. This RCA index shows that Indonesia has strong competitiveness in woven product exports. However, the RCA index of Indonesian woven products in the United States market is still lower than the RCA index of Cina woven products, which is 3.742. Therefore, this study provides suggestions for increasing the competitiveness of woven products so that Indonesia can increase the export value of Indonesian woven products in the United States market.